"Like One Who is Bringing his Own Hide to Market": marx, irigaray, derrida and animal commodification. Issue 2 (2nd April 2016) - Wadiwel, Dinesh Joseph
Abstract: This paper explores the commodification of animals, beginning with Marx's description of how value arises within a system of exchange. Drawing from Irigaray, I observe that value in animals is both arrived at through the use value of the animal as a commodity for human consumption and as a form of currency which serves a function in reproducing the value of the "human" itself. Extending this further, I reflect on Derrida's discussion of the metaphor as a way to understand the removal of the skin of the animal in order to produce value. As I argue, we find here a convergence of material and symbolic violence which produces value in a way which is distinct from other commodities, and participates in generating the "mirage" of human sovereignty over other animals.